Spatial Use Pattern of Lanting House at Kapuas Riverside in the District of Sintang, West Kalimantan - Zairin Zain; Jawas Dwijo Putro (Tesa Arsitektur, 2019)
Houses floatings above water on the banks of the river are the forerunners of settlements that have existed since the past in major rivers such as in the regions of Sumatra, Kalimantan and Papua. People that utilize the potential of rivers will choose to live on those area by built a shelter on water. This dwelling, by local people, is referred to the lanting house. Dwellers will continue to transform the inside of the lanting house to adjust to the needs and to the conditions of the surrounding environment. This adjustment process creates a pattern of spatial use in Lanting houses on the banks of the Kapuas river in Sintang City. This research is classified into basic research with the scope includes a correlation relationship between the use of residential space and variables in the form of occupants and occupancy. The observation method is carried out to obtained data that related to the use of dwelling on the unit space and space layout. As the results of the study, it was found that there was a transformation in the use of inner-space and outer-space. In addition, it was found also a deviation in the pattern of space utilization in the lanting houses in the Kapuas Riverbank in Sintang City. Deviation found as a result of the adaptation process of residents to adapt to environmental conditions. Deviation of functions that occur in lanting house is found in the terrace, living room, family room, and kitchen area. Deviation of function occurs with the addition of new functions. The behavior patterns of the dwellers of the lanting house are influenced to the formation of patterns and floor planning.